Traduzir Lucano em português: ensaio de poética tradutória sincrônica - Vieira, Brunno Vinicius Gonçalves [UNESP] (Universidade Federal do Paraná, 2014)
The aim of this paper is to offer an essay of synchronous translation poetics, based on the theoretic thought of Haroldo de Campos and Antoine Berman, which highlight the relevance of translation history in the work of contemporary translators. For this purpose, starting from a close-reading of the first seven Latin hexameters of Lucan’s Pharsalia, I present a comparative study of the translations of Filinto Elisio (18th century), José Feliciano de Castilho (19th century) and Vieira (2011).
Translating Lucan into Portuguese: an essay on synchronous translation poetics
Keywords: Translation history; Haroldo de Campos; Lucan; História da tradução; Haroldo de Campos; Lucano